2011
DOI: 10.1039/c0cc04973e
|View full text |Cite
|
Sign up to set email alerts
|

Absence of quenching by [Fe(CN)6]4− is not proof of DNA intercalation

Abstract: The quenching of the (3)MLCT emission of three Ru(II) complexes of known DNA binding mode is compared. This work shows that relative binding constants dictate whether quenching is observed in the presence of DNA rather than protection of the probe by intercalation, as has been commonly stated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…x 10 4 L mol −1 , indicating the existence of an interaction with DNA that may be further explored as a molecular biology tool or in therapy, even though being smaller than classics DNA intercalators, such as [Ru(bpy) 2 (dppz)] 2+ (K b = 3.2 x 10 6 L mol −1 ) [31] and [Ru(phen) 2 (dppz)] 2+ (K b = 5.1 x 10 6 L mol −1 ). …”
Section: Dna Titration Monitored By Electronic Absorption Spectroscopymentioning
confidence: 99%
“…x 10 4 L mol −1 , indicating the existence of an interaction with DNA that may be further explored as a molecular biology tool or in therapy, even though being smaller than classics DNA intercalators, such as [Ru(bpy) 2 (dppz)] 2+ (K b = 3.2 x 10 6 L mol −1 ) [31] and [Ru(phen) 2 (dppz)] 2+ (K b = 5.1 x 10 6 L mol −1 ). …”
Section: Dna Titration Monitored By Electronic Absorption Spectroscopymentioning
confidence: 99%
“…We also observe small fluorescence quenching for the complexes without CT-DNA, which indicated that DNA protects complexes from quenchers. Although fluorescence quenching experiment by ferrocyanide cannot be used to prove that DNA protects complexes by intercalation, it can determine DNA affinity of the complex (Burya, Lutterman, & Turro, 2011). Here, the higher quenching efficiency for complex 1 with DNA indicated that it shows lower DNA affinity than complex 2.…”
Section: Emission Titration Experimentsmentioning
confidence: 90%
“…However, it is noteworthy that the absence of quenching by [Fe(CN) 6 ] 4− is not a proof of DNA intercalation. [39] As illustrated in Fig. S1, in .…”
Section: Luminescence Quenching By [Fe(cn) 6 ] 4−mentioning
confidence: 93%